2021
DOI: 10.1063/5.0063726
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of ion-damaged 4H-SiC under thermal and ion beam-induced ultrafast thermal spike-assisted annealing

Abstract: The recovery effect of isochronal thermal annealing and inelastic energy deposited during 100 MeV Ag swift heavy ion (SHI) irradiation is demonstrated in the case of 4H-SiC pre-damaged by elastic energy deposition of 300 keV Ar ion. The Ar-induced fractional disorder follows a nonlinear two-step damage build-up. The fractional disorder level of 0.3 displacements per atom (dpa) is established as the threshold above which the lattice rapidly enters the amorphous phase, characterized by the presence of highly pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…The extent of recovery is found to depend on the amount of surrounding crystalline regions around the amorphous/disordered regions, as evident from the higher recovery observed at the boundaries of the crystalline-amorphous region as compared to the centre. This is consistent with previous studies where it has been concluded that epitaxial recrystallization requires a sufficient amount of crystalline surroundings that acts as the deciding factor for the extent of observed damage recovery [10,11,29,30]. Annealing at 1273 K for 30 min recovers significant damage, however, the RBS/C yield remains much greater than that of the pristine.…”
Section: Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…The extent of recovery is found to depend on the amount of surrounding crystalline regions around the amorphous/disordered regions, as evident from the higher recovery observed at the boundaries of the crystalline-amorphous region as compared to the centre. This is consistent with previous studies where it has been concluded that epitaxial recrystallization requires a sufficient amount of crystalline surroundings that acts as the deciding factor for the extent of observed damage recovery [10,11,29,30]. Annealing at 1273 K for 30 min recovers significant damage, however, the RBS/C yield remains much greater than that of the pristine.…”
Section: Methodssupporting
confidence: 91%
“…A last result to point out is the difference between the 0.7 and 1 dpa irradiated crystals. Indeed, both exhibit an amorphous structure, as shown by RBS/C [11] but, as mentioned earlier, due to the high sensitivity of the synchrotron measurement, it is here possible to discriminate between the two, as a clear difference in the Debye-Wallor factor is readily observed in the 20-180 nm region (see Figure 2(c)).…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations